Potential of autonomous ground-coupled heat pump system installations in Greece - Michopoulos, Apostolos; Papakostas, K. T.; Kyriakis, N. A. (My University, 2011)
The HVAC systems utilizing renewable energy sources are one of the main contributors towards the fossil fuel dependency reduction. Among these, the ground source heat pump systems, especially those based on vertical ground heat exchanger, are very attractive, due to their high efficiency.The size of the systems depends on the building (geometry, construction materials, orientation etc. but also usage and internal gains), on the ground thermophysical characteristics, on the climatology of the area and on the ground heat exchanger design and construction. As a result, the ground heat exchanger length required for heating may result significantly different from the one required for cooling. In this work, the ground heat exchanger lengths required for heating and cooling are calculated for two model-buildings, a residential and an office one, located at 40 different Greek cities, covering a wide range of country's climate conditions. Assuming that a ratio of these lengths in the 0.8-1.2 range is required for efficient long-term operation of the autonomous GSHP system with minimum installation cost, the results suggest that autonomous systems may be used in areas with the heating degree-days in the 800-950. K-days range. In hotter climates with less than 800 heating degree-days, the GSHP system should be supplemented by a conventional cooling system, while in colder climates with more than 950 heating degree-days a conventional heating system supplement is required.
Keywords: Ground source heat pump; Ground heat exchanger; Hybrid ground source air-conditioning system; Autonomous ground source air-conditioning system